Investigation of pico-litre inkjet printing for nano-gram scale solid form screening of pharmaceuticals - Al-Hachami, Wathiq (2018)
The tendency of the majority of active pharmaceutical ingredients (APIs) to exist in different solid forms with keeping their chemical structures is called polymorphism. This phenomenon has gained a lot of interest in the pharmaceutical industry, hoping to avoid producing unexpected transformations of compounds during and after synthesis. The optimal way to avoid that is to subject the API, at the early stage of development, under various conditions in order to obtain an elegant (safe, effective, and stable) drug for the next formulation step. The aim of this thesis was to investigate some factors that affect the appearance of different polymorphs during screening of some APIs. Four model drugs were selected: paracetamol; carbamazepine; mefenamic acid; and flufenamic acid. All have been well-characterised previously in terms of solid-state forms. Piezoelectric, or 2D inkjet printing technique was used as a main technique in fabrication of nanoarrays of APIs onto predefined design on a solid tunable substrates because of its ability to control the delivered quantities of the the printed materials accurately, without any direct contact with the used substrate that may cause a sample cross-contamination. Light optical microscope was used to investigate the behaviour of the printed droplets during and after solvent evaporation and turn to dried spots, and to confirm the crystalline state of some spots by using the polarised light in the same microscope. Raman spectroscopy at low-wavenumber, or phonon region (40-400 cm-1) was used for the first time to identify the resulted polymorphs after the printing process as its ability to probe the alterations that happen in the molecular skeleton inside the crystal lattice , in addition to molecular region (400-1800 cm-1) to analyse the resulting spots. In chapter three, the piezoelectric inkjet printing technique was successfully used for the first time to miniaturise, screen, and study the stability of the APIs at nano quantities in the range of (1-500 ng), about six-ordered magnification less than the reported studies. It was found that the variation in the printed quantities can produce different states and polymorphs. Stability with time was also studied for all the printed samples and it was noticed the variation in time for some printed drugs to convert from solid amorphous to crystalline state.